PENGARUH PENGGUNAAN E-FILING, E-BILLING DAN E-FAKTUR TERHADAP KEPATUHAN WAJIB PAJAK BADAN - Julang Aprianto; Fajar Harimurti; Bambang Widarno (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the effect of e-filling, e-billing and e-invoicing on corporate taxpayer compliance in the Pratama Tax Service Office Surakarta. This type of research is a survey study on corporate taxpayers at KPP Pratama Surakarta. The population of this research is all corporate taxpayers registered in Pratama Tax Service Office Surakarta. The sampling technique used purposive sampling with a sample of 93 corporate taxpayers. The technique of collecting data used a questionnaire. The data analysis technique used is multiple linear regression. The results showed that e-filling had a positive and significant effect on corporate taxpayer compliance at the Pratama Tax Service Office Surakarta. e-billing hasda positive and significant effect on corporate taxpayer compliance at the Pratama Tax Service Office. e-invoices have a positive and significant effect on corporate taxpayer compliance at the Pratama Tax Service Office Surakarta.